Jokes Have a Laugh and Improve Your English - Wallwork, Adrian (Easy English!,, 2018)
Jokes are a perfect format for learning vocabulary, idiomatic expressions, and grammar. Jokes are also designed to be retold. If you learn a joke by heart and tell it to other people, then by doing so you will also learn the grammar and vocabulary involved. The book also contains exercises designed to reveal whether you have understood the joke or not: A joke is presented to you but with the paragraphs mixed up. Your task is to put them in the correct order. The joke has a choice of three punch lines. If you select the correct one, this should be an indicator that you have understood the joke. Several two-line jokes are presented together. The task is to match the first line and the second line. A joke is presented with some key words missing. The task is to insert the right word in the right place. Easy English! is a series of books to help you learn and revise your English with minimal effort. You can improve your English by reading texts in English that you might well normally read in your own language e.g. jokes, personality tests, lateral thinking games, wordsearches. doing short exercises to improve specific areas grammar and vocabulary, i.e. the areas that tend to lead to the most mistakes - the aim is just to focus on what you really need rather than overwhelming yourself with a mass of rules, many of which may have no practical daily value Other books in the Easy English! series include: Wordsearches: Widen Your Vocabulary in English Test Your Personality: Have Fun and Learn Useful Phrases Word games, Riddles and Logic Tests: Tax Your Brain and Boost Your English Top 50 Grammar Mistakes: How to Avoid Them Top 50 Vocabulary Mistakes: How to Avoid Them.